Mapping relational data model to OWL ontology: knowledge conceptualization in OWL - Zhao, Shuxin; Wongthongtham, Pornpit; Dillon, Tharam S.; Chang, Elizabeth (Institute of Electrical and Electronics Engineers (IEEE), 2008)
In this paper, we introduce the issues and solutions of using OWL ontology to model extra restriction on 'Properties' of 'Classes' that are not provided by OWL specifications and to represent associations amongst 'Properties' other than 'Classes'. Two specific types of knowledge that cannot be modeled directly using OWL DL elements are identified and presented. Firstly the data value range constraint for a "DatatypeProperty"; secondly the calculation knowledge representation. Our approach to such issues is to conceptualize the knowledge in OWL and map the conceptualization in an implementation. Examples for each type of the knowledge and their OWL code are provided in detail to demonstrate our approach.